1957
DOI: 10.2136/sssaj1957.03615995002100020022x
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Methods for Determining Extractable Soil Potassium in Fertilizer Test Plots1

Abstract: A Bridgehampton silt loam which had received various amounts of potassium fertilizers for 44 years was analyzed for extractable or exchangeable K by 6 methods. Total K and that removed by boiling IN HNO 3 were also deter mined. The methods measured significantly different quantities of K. The PeechEnglish method extracted more than did the North Carolina, Maine, or Morgan pro cedures. Neutral normal ammonium acetate extraction and a method employing IR120 resin (Amberlite) were inter mediate. The use of exchan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

1961
1961
2002
2002

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Hydrogen-saturated resins have been used for this purpose by Pratt (1951), Schmitz and Pratt (1953), Salomon and Smith (1957), Arnold (1958), MacLean (1961, Stahlberg (1959), Scott et al (1960), Barber and Mathews (1962), Miller (1963), Feigenbaum et al (1981), and Martin and Sparks (1983). These resins have high cation-exchange capacities, far exceeding those of soils.…”
Section: Cation-exchange Resinsmentioning
confidence: 99%
“…Hydrogen-saturated resins have been used for this purpose by Pratt (1951), Schmitz and Pratt (1953), Salomon and Smith (1957), Arnold (1958), MacLean (1961, Stahlberg (1959), Scott et al (1960), Barber and Mathews (1962), Miller (1963), Feigenbaum et al (1981), and Martin and Sparks (1983). These resins have high cation-exchange capacities, far exceeding those of soils.…”
Section: Cation-exchange Resinsmentioning
confidence: 99%
“…Since then, ion exchange resins have been adopted to measure the amounts of plant-available nutrient ions in soils and the rates at which they are released (Salomon and Smith 1957;Bowman et al 1978;Martin and Sparks 1983;Skogley et al 1990). To date, based on our literature search, there have been about 400 journal articles published.…”
mentioning
confidence: 99%
“…Use of resins for extracting soil K has also been investigated (11). However, little work has been done using ion exchange resins for extracting soil Zn.…”
mentioning
confidence: 99%
“…However, little work has been done using ion exchange resins for extracting soil Zn. Salomon and Smith (11) found that use of exchange resin appeared to be more effective in estimating crop response to K fertilizer than buffered acetate solutions. Moser et al (7) concluded that an ion exchange resin method of estimating soil P concentration demonstrated greater precision in predicting P uptake than routine chemical extractants.…”
mentioning
confidence: 99%